A Pilot Investigation into Spatiotemporal Gait Differentiation Between Competitive and Recreational Runners Using OptoGait Technology - Yu, JaeHo (Journal of Neonatal Surgery, 2025)
Purpose: This pilot investigation aims to elucidate biomechanical disparities in gait characteristics between competitive and recreational runners through high-resolution spatiotemporal assessment using the OptoGait system. The goal is to discern performance-enhancing mechanisms and injury susceptibility patterns across varying athletic populations. Methods: A cross-sectional, quasi-experimental study design was employed involving thirteen adult participants (6 competitive, 7 recreational), evaluated using an instrumented treadmill integrated with OptoGait optical sensors. Spatiotemporal parameters such as stride length, contact time, flight time, cadence, and angular displacement were quantified and statistically analyzed via independent t-tests (p < 0.05). Results: Competitive runners exhibited a significantly elevated step cadence (161.00±0.89 steps/min) and reduced step angle (0.54±0.01 rad) relative to recreational runners (157.71±2.05 steps/min, 0.57±0.01 rad), with a notable reduction in step length (103.50±1.04 cm vs. 107.29±1.38 cm, p < 0.001). No significant intergroup differences emerged in contact and flight times. Conclusion: This comparative gait analysis underscores distinct biomechanical adaptations among competitive runners characterized by a more compact stride, heightened cadence, and attenuated angular strike pattern—features conducive to running economy and injury mitigation. These findings support the utility of individualized training paradigms and biomechanical profiling for optimizing performance outcomes and preventive strategies in heterogeneous runner cohorts.Keywords: Digital therapeutics, Dual Task, Proprioceptive Exercise, Postural Stability, Positioning Sensation, Cognition